ANALISIS NILAI-NILAI PENDIDIKAN KARAKTER PADA CERPEN “TANAH AIR” KARYA MARTIN ALEIDA PERAIH TERBAIK KOMPAS TAHUN 2016 - Christine Permata Irawan; Agris Yuni Rispandi; Achmad Fauzi; Diena San Fauziya (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This study aims to describe the values in the works of short stories "Homeland" by Martin Aleida. The method used is descriptive method. The type of research is literature research. The object of research is the short story of "Land of Water" by Martin Aleida the best winner of the compass of 2016. Data technique by searching data about the variables that are short stories, looking for items and short stories that contain the values of characters, character values, analyzing and interpreting data in accordance with the keywords created, grouping the value of characters, describing the value of characters contained in the short story and the conclusions of the analysis of the values in the short story. Data analysis techniques using content analysis. The pattern of withdrawal of the conclusion used the deductive pattern or inductive short story later. Through this research, the values of character education that exist in the short story "Fatherland" is the love of the homeland or spirit of nationality, responsible, honest, caring for the environment, independent, and affection.